Analyzing Writing Difficulties in The Beginning Writing of Second Grade Elementary School Students - Ida Farida; Dayu retno Puspita; Septy Nurfadhillah (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2019)
This study aims to analyze difficulties and its causing factors from the beginning writing of second-grade students in one of the elementary schools in Tangerang, Indonesia. This research used descriptive qualitative method. The data collected from the research results were described in the form of words. The results of this study were found in 28 students' writings that have been analyzed, as many as 75% of students have been completed in learning to start writing and 25% of students have not finished writing in the beginning due to factors such as difficulties in fine motor skills, difficulty in perception of visual-motor coordination and visual memory difficulties. Students' difficulties were assessed from the aspect of beginning writing, namely: students' difficulty in the formation of formations, neatness of writing, spaces, form accuracy, proportions, and quality of writing lines.Keywords: Learning Difficulties; Writing; Writing Beginning. AbstrakPenelitian ini bertujuan untuk mengetahui kesulitan siswa dalam menulis permulaan dan faktor penyebab kesulitan menulis permulaan pada siswa kelas 2 di salah satu Sekolah Dasar di Tangerang. Metode yang digunakan dalam penelitian ini adalah metode kualitatif deskriptif, yaitu mengkaji dan menganalisis data secara objektif sesuai dengan data yang ditemukan dilapangan. Kemudian data yang terkumpul dari hasil penelitian di deskripsikan dalam bentuk kata-kata. Hasil penelitian ini di temukan pada 28 tulisan siswa yang telah dianalisis, sebanyak 75% siswa sudah tuntas dalam pembelajaran menulis permulaan dan 25 % siswa belum tuntas dalam menulis permulaan dikarenakan antara lain faktor kesulitan dalam motorik halus, kesulitan persepsi koordinasi visual motorik dan kesulitan visual memori dan kesulitan siswa dinilai dari aspek menulis permulaan yaitu: kesulitan siswa dalam susunan formasi, kerapian tulisan, spasi, ketepatan bentuk, proporsi dan kualitas garis tulisan.Kata Kunci: Kesulitan Belajar; Menulis; Menulis Permulaan.